Microwave-assisted synthesis of palladium nanoparticles supported on copper oxide in aqueous medium as an efficient catalyst for Suzuki cross-coupling reaction - Hany A Elazab; M.A. Sadek; Tamer T El-Idreesy (Adsorption Science & Technology)
We report here a reliable green method for the synthesis of palladium nanoparticles supported on copper oxide as a highly active and efficient catalyst for Suzuki cross-coupling reaction. The experimental synthetic approach is based on microwave-assisted chemical reduction of an aqueous mixture of palladium and copper salt simultaneously using hydrazine hydrate as reducing agent. The catalyst was fully characterized using various techniques showing well-dispersed palladium nanoparticles. The catalytic activity and recyclability of the prepared catalyst were experimentally explored in the ligand-free Suzuki cross-coupling reaction with a diverse series of functionalized substrates. The synthesized Pd/CuO catalyst shows many advantages beside its high catalytic efficiency such as the recyclability of up to five times with negligible loss of catalytic activity, short reaction times, use of environmentally benign solvent systems, and mild reaction conditions.